(untitled) (Historia, 2021)
Academics and others interested in the VOC are cordially invited to attend the above Conference. The 400th anniversary of the founding of the Dutch East India Company (VOC) in 1602, and the 350th anniversary of its settlement at the Cape in 1652, will both be commemorated in 2002. This Conference is one of a number of commemorative occasions by which the VOC Foundation hopes to draw attention to the VOC and its activities world wide. Academics from the Netherlands, Belgium, Indonesia, Australia, the USA and South Africa, representing a variety of research areas have already indicated their interest in the Conference.Other programs commemorating the founding of the VOC in 1602 and the settlement of the VOC at the Cape in 1652, will be presentedat the Castle of Good Hope, Cape Town, on the 20th of March and the 6th of April 2002.